Multi-specialization: The concept, motivations and impact on individuals - Rui Miguel Dias Carvalho; Patricia Jardim da Palma (Arab Economic and Business Journal, 2018)
We present the concept of multi-specialization for those building careers, which refers to workers becoming very familiar with two or three fields of knowledge. This requires a compromise between individual capacity and individual learning needs and also means that workers will need to maintain or achieve higher levels of productivity, ensuring or enhancing social welfare. Taking into account the differences between this concept and the traditional concepts of single-field specialization, we were able to uncover and highlight several positive possible results that many workers expect to experience when adopting this work perspective and, at the same time, to hear their concerns. A questionnaire and a set of interviews allow us to understand the individual experiences of those studied in this context.
Keywords: 650; Multi-specialization; productivity; Behaviors; Well-being